Strategi Pembelajaran Metode RADEC : berfikir kritis dan kreatif pada hasil produk ecoprint mahasiswa - Noerharyono, Muchamad; Suliyanthini, Dewi; Br Ginting, Florentina; Haerunnisha, Icha; Febrilias, Arsyanda (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
The purpose of this study was to measure the process of student creativity in make ecoprint motif products on textile fabrics, with project-based learning, by applying the Radec learning model; (Read)-Reading; (Answer)-answer; (Discussion)- discussion, (Explain)-practice; (Creativity)-creative. The research method was quantitative experiment Research and development ADDIE model, on the final product of student ecoprints. The research sample was 60 students with control class. The results of the research a significant minimum increase in creative thinking skills in control group scores among students from pre-test (M=62.3, SD=2.84) to post-test (M=65.4, SD=2.47), t(29)=4.54 with Ï-value=0.001<0.05, indicating significance creative thinking skills among students